Intergenerational spillover effects of school-based disaster education: Evidence from Indonesia. (1st February 2023) - Harada, Tetsuya; Shoji, Masahiro; Takafuji, Yoko
Abstract: The literature demonstrates that school-based disaster education is a cost-effective approach to facilitate children's attitudes, knowledge, and behavior regarding disaster risk reduction. However, effective interventions for adults are not yet well understood. The goal of this study is to evaluate the spillover effects of a disaster education program for children on their parents. Unique survey data were collected from 539 elementary school students and their parents on Nias Island, Indonesia, among whom 214 students participated in the Maena for Disaster Education program. The results using an instrumental variable model show that the program encourages children to discuss and share knowledge about disasters with their parents, and has positive effects on parents' attitudes, knowledge, and behavior. This impact is particularly large for households residing in risky areas. Therefore, school-based disaster education is effective not only for the participants but also for their parents, suggesting there is a substantial social impact. This is the first study to rigorously demonstrate the spillover effects of disaster education on parents in a developing country. This study also contributes to the literature on intergenerational value transmission by applying an instrumental variable model and providing direct evidence.